Design thinking dalam Mata Pelajaran Desain Komunikasi Visual sebagai Upaya Meningkatkan Kemampuan Penyelesaian Masalah dan Mencipta - Anwar, Ruri Restia; Bachri, Bachtiar S.; Kristanto, Andi (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This study aims to determine the application of the Design thinking method in Visual Communication Design learning to improve problem solving skills and create students. The Design thinking method combines creative and analytical approaches, has been applied in various industries as a tool to overcome complex challenges. However, its application in education is still relatively new, especially in the subject of Visual Communication Design. This research uses a qualitative approach by applying case study strategies in the Visual Communication Design learning environment. Data was collected through classroom observation, interviews with teachers and students, and analysis of creative products produced by students during the learning process. The results showed that the application of Design thinking significantly improves students' ability to identify, analyze, and solve complex problems in the context of visual communication design. In addition, this study also revealed that the application of Design thinking positively affects students' ability to create. Overall, this study concludes that the application of Design thinking in Visual Communication Design subjects has great potential in improving problem-solving and creating abilities. The practical implications of this research point to the need for further exploration in integrating these methods into broader learning approaches, with the aim of producing students who are able to face real-world challenges with creativity and confidence.